Surface Passivation Effect of Hydrogen and Methyl on the Structural and Electronic Properties of Silicon Quantum Dots: Density Functional Calculation - Muhammad Mus-'ab Anas; Geri Gopir (Trans Tech Publications, Switzerland, 2024)
Volume 846